Forensic Assistance Project: Consultant Report 1999-030 Kasindol I Federation Commission on Missing Persons - Bosniak Side - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Stuart, Gary On 23 June 1999 the Federation Commission on Missing Persons - Bosniak Side investigated a suspected grave in the Bosnian Serb sector of Sarajevo in an area referred to as Kasindol, Republika Srpska. Reportedly Bosnian Serb paramilitary soldiers killed three Bosniak soldiers in 1992 in the Kasindol region. Allegedly the remains of the three victims were buried on a hillside above a stadium in Kasindol. The suspected gravesite was searched by members of the exhumation team for 1 hour. No remains were identified and the site was abandoned. Place of Exhumation: Kasindol Date of Exhumation: 23 June 1999 Minimum Number of Exhumed Individuals: 000